Highly Efficient Circularly Polarized Radial Line Slot Array Antenna Using Non-Uniform Slot Density for 5G Communication System - Cumurcu, Onur; Torpi, Hamid; Caliskan, Alper (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2023)
Radial Line Slot Array (RLSA) antennas have appealing features including high gain and high efficiency combined with a low profile. Especially by highlighting their structural simplicity, RLSA antennas can be good competitors to reflector antennas if the efficiency parameters are improved. In this article, a novel approach is presented to improve the aperture efficiency of RLSAs, with a significant increase of around 10% being achieved. The core principle of this method is the use of non-uniform slot density on the RLSA antenna rings, in addition to non-uniform slot length. RLSA antennas consist of many spiral rings and slots are placed on these rings. With the help of new the concept, slot density has been increased especially on the outer spiral lines, and thus significant improvement has been achieved in both aperture efficiency and return loss. In order to verify the concept, a prototype antenna was fabricated at 26 GHz. The measured results of the prototype antenna show an excellent aperture efficiency of 45%, peak gain of 30.3 dB, and axial ratio of less than 3 dB at operating the frequency band. Also, the antenna reflection coefficient value is less than -10 dB between 24.75 GHz and 27.5 GHz and side lobe levels are below 18 dB, which indicate good pattern characteristic.
Keywords: Aperture efficiency; high gain; microwave link; radial line slot array; side lobe; 5G; TV; REFLECTOR; Computer Science; Engineering; Telecommunications